SPE Middle East Oil and Gas Show and Conference 2009
DOI: 10.2118/120205-ms
|View full text |Cite
|
Sign up to set email alerts
|

Steamflood Piloting the Wafra Field Eocene Reservoir in the Partitioned Neutral Zone, Between Saudi Arabia and Kuwait

Abstract: The concept of steamflooding the Wafra Eocene dolomite reservoir originated in various studies conducted in the 1980's. In 1999, a comprehensive EOR study and Eocene huff-n-puff pilot suggested that steamflooding could be a viable recovery process for the reservoir. As a result of these studies, a staged development approach was incorporated to test the viability of pattern steamflooding the Eocene reservoir. The objective was to assess key technical challenges associated with steamflooding an anhydrite and gy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…The screening studies were confirmed by dynamic modeling and economic analyses, which led to the decision for a steamflood pilot (Barge et al 2009). The initial pilot small scale test (SST) consisted of a single 1.25-acre inverted five spot with central injector and one temperature observation well (TOW).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The screening studies were confirmed by dynamic modeling and economic analyses, which led to the decision for a steamflood pilot (Barge et al 2009). The initial pilot small scale test (SST) consisted of a single 1.25-acre inverted five spot with central injector and one temperature observation well (TOW).…”
Section: Introductionmentioning
confidence: 89%
“…3. Steam injection at the SST began in 2006 and currently continues primarily to evaluate scale-and corrosionmitigation options (Barge et al 2009). Steam injection into the LSP C-Zone, which is the focus of this paper, began in 2009.…”
Section: Introductionmentioning
confidence: 99%
“… Cyclic steam injection pilot in Issaran heavy oil field, Egypt [183].  Steamflood pilot at the giant Wafra Field, Kuwait-Saudi Arabia [184,185].…”
Section: Thermal Methodsmentioning
confidence: 99%
“…The pilot operations are tried in France, Italy, Congo, Turkey, USA, Kuwait, and Saudi Arabia [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. The first part of the data collected and used in this study is from field pilots of steamflooding in VO NFCRs reported in the literature.…”
Section: Data Collectionmentioning
confidence: 99%